EFFECTIVE WASTE MANAGEMENT FOR SUSTAINABLE TERTIARY EDUCATION DEVELOPMENT IN NIGERIA - Ayoko, Victor Olugbenga (Multi-Disciplinary Research and Development Journals Int’l, 2025)
This paper discussed the effective waste management for sustainable tertiary education development in Nigeria. Depending on secondary data obtained from recognized online and print resources. The paper concluded that waste reduction at the source, recycling and reuse programs, composting of organic waste, proper segregation of waste, safe disposal of hazardous and electronic waste, integration of waste management into curriculum and research, community engagement and stakeholder collaboration and monitoring, evaluation, and policy implementation are some of the effective waste management practices tertiary institutions in Nigeria can adopt to enhance environmental sustainability in their respective institutions. Based on the findings, the paper recommends the establishment of comprehensive waste management policies, investment in waste management infrastructure, promotion of awareness and capacity building, integration of waste management into academic programs, foster collaboration with external stakeholders, encourage waste reduction at the source, implement regular monitoring and evaluation, provide incentives for sustainable practices, address hazardous and electronic waste safely and promote green campus initiatives.